Salt, Hypertension and Cardiovascular Disease: the Connection - Arieska Ann Soenarta (The Indonesian Heart Association, 2011)
Hypertension (HT) the most important risk factor of cardiovascular disease (CVD), is a heterogeneous disease; the underlying cause is unknown. Genetic back-ground and environmental influences are both involved. The most important environmental fac-tors are physical inactivity and dietary factors, particularly salt and potassium intake.There is a relationship between Blood Pressure (BP) and natriuresis which maintains sodium bal-ance and extra cellular fluid volume. An impaired ability of the kidney to excrete sodium, requires an increase in BP to increase natriuresis and correct sodium balance resulting in HT. Much evidence suggests, that in those who develops high BP, there is an underlying defect in the ability of the kidney to excrete salt and that the greater compensatory response required to restore sodium balance is the cause for the increase in BP.Epidemiological, mi-gration, intervention, treatment, genetic and animal studies have shown that dietary salt (sodium chlo-ride) plays an important role in BP regulation. The INTERSALT study, the EPIC-Norfolk study and many other studies have shown that BP was higher among subjects with a high sodium intake.